Jawabanmu

2014-04-20T20:35:24+07:00
lim x-->π/4 cos 2x = lim x-->π/4      cos²x - sin²x
                 1-tan x
                    (cosx/cosx - sinx/cosx)

                           = lim x-->π/4 (cos x + sinx)(cosx - sinx)
                                                     (cosx - sinx)/cosx
                          = lim x-->π/4 cosx (cos x + sinx)(cosx - sinx)
                                                     (cosx - sinx)
                         = lim x-->π/4 cosx(cosx + sinx)
                         = cosπ/4(cosπ/4 + sinπ/4)
                         = √2/2(√2/2 + √2/2)
                         = √2/2(√2)
                         = 2/2
                         = 1
2014-04-20T21:17:44+07:00
= lim x-->π/4 cosx(cosx + sinx)
                         = cosπ/4(cosπ/4 + sinπ/4)
                         = √2/2(√2/2 + √2/2)
                         = √2/2(√2)
                         = 2/2
                         = 1